2015
DOI: 10.1016/j.chemosphere.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Novel methods for measuring air–water interfacial area in unsaturated porous media

Abstract: Interfacial partitioning tracer tests (IPTT) are used to measure air-water interfacial area for unsaturated porous media. The standard IPTT method involves conducting tests wherein an aqueous surfactant solution is introduced into a packed column under unsaturated flow conditions. Surfactant-induced drainage has been observed to occur for this method in some cases, which can complicate data analysis and impart uncertainty to the measured values. Two novel alternative approaches for conducting IPTTs are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 22 publications
(27 reference statements)
6
56
0
Order By: Relevance
“…This is identical to the independently measured value. The mean measured K d determined from the mass-balance tests for Vinton is 0.51, which is very similar to the independently measured value of 0.5 (Brusseau et al, 2007, 2015). These results indicate that the test procedures (extractions, chemical analysis) produced robust measures of tracer distribution.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This is identical to the independently measured value. The mean measured K d determined from the mass-balance tests for Vinton is 0.51, which is very similar to the independently measured value of 0.5 (Brusseau et al, 2007, 2015). These results indicate that the test procedures (extractions, chemical analysis) produced robust measures of tracer distribution.…”
Section: Resultssupporting
confidence: 83%
“…The magnitude of the retardation corresponds to the magnitude of the interfacial area. The miscible-displacement (MD) IPTT data presented in the figures were previously reported by Brusseau et al (2007, 2015).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Corley et al (1996) showed that low concentrations of volatile organic compounds distribute in the bulk phases (air, water, and solid), adsorb to the air-water interface, and partition into intraparticle pores in unsaturated and saturated porous media. While it has been demonstrated in experiments that the gas-water interface poses a high potential for retardation (Brusseau et al, 1997;Costanza-Robinson and Brusseau, 2002b), determining the effective interfacial area, which controls the contaminant mass transfer, is still subject of intensive research (Goss, 2009;Kibbey and Chen, 2012;Brusseau et al, 2015). Mayes et al (2003) stated that immobile water in pores could act as a short-term sink and as a long-term source of potential contaminants.…”
Section: Introductionmentioning
confidence: 99%